Assessment of Combining Ability for Productivity and Quality Traits in Aromatic Rice (Oryza sativa L) - Mohammad, Naseer; Singh, Surendra; Ahmad, Ekhlaque; Tewari, Salil (International Journal of Bio-resource and Stress Management, 2016)
Analysis of combining ability in relation to mean performance, morphometric and quality parameters in aromatic rice holds vital importance for improvement. The present experiment was carried out to study the general combining ability of eight aromatic varieties and specific combining ability of their all possible crosses for grain yield and quality traits. The analysis of variance for combining ability revealed that the GCA and SCAvariances were significant for all characters under study except panicle length. It showed that both the additive as well as non-additive genetic variance were important for expression of the characters studied. The variance due to SCA (σ2s) was higher than GCA (σ2g) for days to flowering, plant height, flag leaf length, number of effective tillers plant-1, panicle length, number of spikelets panicle-1, seed yield, biological yield plant-1, harvest index, hulling recovery, milling recovery, head rice recovery, dehulled kernel length, dehulled kernel breadth, L/B ratio, cooked kernel length, cooked kernel breadh, cooked kernel L/B ratio, elongation ratio, alkali digestion value, gel consistency and amylose content suggesting significant role of non additive gene actions like dominance, epistasis and other interaction effects in the expression of these characters. The GCA effects of the parents indicated that the parent, Pant sugandh Dhan-17 to be the best general combiner. Crosses, Sugandhmati×Pant Sugandh Dhan-15, Sugandhmati×Pant Sugandh Dhan-17, Pant Sugandh Dhan-15×Taraori basmati and Pant Sugandh Dhan-15×Pant Sugandh Dhan-17 exhibited significant sca effect for seed yield and can be exploited by heterosis breeding.